2019
DOI: 10.1093/ajh/hpz133
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Socioeconomic Status and Hypertension in African American Adults: The Jackson Heart Study

Abstract: BACKGROUND Limited research has examined the association of life-course socioeconomic status (SES) with hypertension prevalence and incidence in a large cohort of African Americans. METHODS Among 4,761 participants from the Jackson Heart Study (JHS), we examined the association of SES indicators with prevalent and incident hypertension. We used multivariable Poisson regression to estimate prevalence ratios (PR, 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
2
36
1
2
Order By: Relevance
“…That may contribute to the higher odds of hypertension among rich individuals. Contrary to this finding, a longitudinal cohort study among African Americans showed that the odds of hypertension lower among rich individuals [ 45 ]. A meta-analysis on socioeconomic status and hypertension indicate similar finding, which was an increase in the odds of hypertension among low socio-economic status.…”
Section: Discussionmentioning
confidence: 90%
“…That may contribute to the higher odds of hypertension among rich individuals. Contrary to this finding, a longitudinal cohort study among African Americans showed that the odds of hypertension lower among rich individuals [ 45 ]. A meta-analysis on socioeconomic status and hypertension indicate similar finding, which was an increase in the odds of hypertension among low socio-economic status.…”
Section: Discussionmentioning
confidence: 90%
“…Living in poverty and low SES increases the risk of myocardial infarction [ 15 , 16 ], having higher blood pressure and body mass index [ 17 19 ], reduced neuroanatomic health in white matter integrity [ 20 ] and hippocampal volume [ 21 ], and development of diabetes mellitus [ 22 , 23 ]. AAs living in poverty are at an increased risk for early mortality, particularly among AA men [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hollister et al address this challenge by applying their recently validated algorithm that defines socioeconomic status using electronic health records (Hollister et al, 2017 ) to a large clinical population of African American patients. All patients were clinically screened for hypertension, a complex condition disproportionately prevalent in African Americans (Fryar et al, 2017 ) that is independently associated with many common genetic variants and environmental exposures such as diet and socioeconomic status (Aburto et al, 2013 ; Giri et al, 2019 ; de las Fuentes et al, 2020 ; Glover et al, 2020 ; Hollister et al ). In the work presented herein, Hollister et al tested for and possibly identified a statistical interaction between education, a recognized social determinant of health, and genetic variants contributing to blood pressure, underscoring the need for additional study of the potentially modifying effects of non-genetic factors for diseases with noted population differences.…”
Section: Social Determinants Of Health and Genetic Association Studiementioning
confidence: 99%